Fifty-second symposium of the Society for General Microbiology, held at the University of Leicester, January 1995 (Cambridge, Massachusetts, 1995)
The book brings together authoritative articles summarizing the current state of knowledge of the genetic organization of bacterial populations. It includes the evolution of E. coli populations, the roles of gene transfer and recombination, the distribution and evolution of plasmids nad antibiotic resistance, population genetics of phase-variable systems, population dynamics and epidemiology of bacterial pathogens, and plasmid transfer in the natural environment. Similarities to and differences from the population genetics of higher organisms are emphasized throughout, and the impact of bacterial studies on current evolutionary theories highlighted. The consequences of population structure in clinical practice, environmental situations and commercial exploitation of bacteria are also considered
Keywords: bacterial genetics - congresses,population genetics - congresses